Effect of Bosswelic Acid On Hematological Parameters In Sprague Dawley Rats (Rattus novergicus) Induced By Cyclophosphamide - Maret Daulay, Lingga Surya; Wientarsih, Ietje; Esfandiari, Anita; Sutardi, Lina Noviyanti; Asmilia, Nuzul (Asian Journal of Social and Humanities, 2024)
Chemotherapy drug “cyclophosphamide (SP)” can trigger oxidative stress that causes hematotoxicity and myelotoxicity, therefore an agent that can suppress the negative effects of cyclophosphamide is needed. Boswellic acid is an herbal medicine that has anti-oxidant and anti-inflammatory effects. The aim of this study was to determine the effect of boswellic acid (BA) in hematology parameter rats induced by cyclophosphamid. Animal were allocated in to six groups, each group consists of 5 rats, the KS: healthy group, KSP: cyclophosphamide group; KSD: comparison group, and BA groups (K1;K2;K3). The treatment groups were given cyclophosphamide (SP) at dose of 150 mg/kg body weight (BW) i.p. The BA groups (K1,K2,K3) were given BA at dose of 250 mg/kg BW orally for 6 consecutive days and SP on day 1 (K1), day 4 (K2), day 6 (K3). The results showed that BA administration (K2 and K3) can help increase/maintain the amount of hematological parameters including hemoglobin, hematocrit, and erythrocytes. Administrating BA for 6 days consecutively before SP (K3) has shown best results on hematological parameters than the others including the comparison group. These results suggest that BA may have a potential herbal therapeutic agents that can mitigate cyclophosphamide-induced hematotoxicity manifestations.